Synthesis of novel Co3O4 nanocubes-NiO octahedral hybrids for electrochemical energy storage supercapacitors. (15th November 2021) - Reddy, N. Ramesh; Reddy, P. Mohan; Mandal, T.K.; Reddy, Kakarla Raghava; Shetti, Nagaraj P.; Saleh, Tawfik A.; Joo, Sang Woo; Aminabhavi, Tejraj M.
Abstract: Fabrication of novel metal oxide nanostructured composites is a proficient approach to develop efficient energy storage devices and development of cost-free and eco-friendly metal oxide nanostructures for supercapacitor applications received considerable attention in recent years. The Co3 O4 nanocubes-NiO octahedral structured composite was constructed using facile and one-step calcination process. Cyclic voltammetry, charge-discharge, and electrochemical impedance spectral techniques have been employed to analyze the specific capacitance of the synthesized nanostructures and the composites. Specific capacitance and cycling stability of the composites were evaluated with the pristine Co3 O4 and NiO nanostructures. The composite showed a specific capacitance of 832 F g −1 at a current density of 0.25 A g −1, which was 1.5 and 1.9-times higher than pristine Co3 O4 nanocubes and NiO octahedral structure, respectively. On the other hand, electrode showed approximately 50 % capacity retention at a higher current density (5 Ag -1 ) because of the uniform morphology of Co3 O4 and NiO. The charge-discharge stability measurements of the composite showed an admirable specific capacitance retention capability, which was 94.5 % after 2000 continuous charge-discharge cycles at a current density of 5 A g −1 . The superior electrochemical performance of the nano-composite was ascribed to synergistic effects and uniform morphology. Efficient nanostructure development using facile and one-step calcination process and electrochemical performance make the synthesized composite a promising device for supercapacitor applications. Graphical abstract: Image 1 Highlights: Heterostructured Co3 O4 –NiO hybrids were synthesized through calcination process. Physico-chemical and electrochemical energy storage super-capacitive properties investigated. Hybrid electrode showed specific capacitance of 832 F g −1 at a current density of 0.25 A g −1 Hybrid electrode showed capacitance retention of 94.5 % after 2000 charge-discharge cycles. Co3 O4 –NiO hybrids showed energy density of 42 Wh kg −1 at power density of 183 W kg −1